Novelty Seeking in Patients with Right- Versus Left-Onset Parkinson Disease. Issue 1 (March 2015) - Harris, Erica; McNamara, Patrick; Durso, Raymon
Abstract : Objective and Background: In patients with Parkinson disease, the personality trait "novelty seeking" has been linked to higher-than-normal risk for impulse control disorders. We measured novelty seeking to test whether side of onset of Parkinson disease predicted patients' risk for impulsivity. Methods: We evaluated 38 patients with Parkinson disease (19 right onset, 19 left onset) and 44 community-dwelling neurotypical controls. All participants completed demographic and mood measures and the Temperament and Character Inventory personality questionnaire. The right- and left-onset groups were nearly the same in background and clinical variables, including use of dopamine agonists. Results: The patients with right-onset disease exhibited significantly higher levels of novelty seeking than the patients with left-onset disease. Conclusions: Our results suggest that patients with right-onset Parkinson disease who are taking dopamine agonists and who exhibit high novelty seeking are at greater risk for developing impulse control disorders than are patients with left onset who are also taking dopamine agonists.